If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1 + -1x = 7 + x + 3 Reorder the terms: 1 + 3x + -1x = 7 + x + 3 Combine like terms: 3x + -1x = 2x 1 + 2x = 7 + x + 3 Reorder the terms: 1 + 2x = 7 + 3 + x Combine like terms: 7 + 3 = 10 1 + 2x = 10 + x Solving 1 + 2x = 10 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + 2x + -1x = 10 + x + -1x Combine like terms: 2x + -1x = 1x 1 + 1x = 10 + x + -1x Combine like terms: x + -1x = 0 1 + 1x = 10 + 0 1 + 1x = 10 Add '-1' to each side of the equation. 1 + -1 + 1x = 10 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 10 + -1 1x = 10 + -1 Combine like terms: 10 + -1 = 9 1x = 9 Divide each side by '1'. x = 9 Simplifying x = 9
| -8z-7z=-3z-5-9z | | x^2+3n=0 | | 18b^4=15 | | 6=8x-7 | | 5x+9=-2x+2 | | 18x-1=14x-21 | | 4x+9x-6x-5=30 | | -7y-2=-6y-5 | | X+6=7x+5 | | 12y+54x-6=0 | | 45+x=0.1(900+x) | | -4(1-3r)=-100 | | 4x^2+5x+c=0 | | 5y+3x=60 | | 55r^2+4r-3= | | 2(3x+6)=-14+8 | | 8/5/6-10/1/12= | | 3x+18=6x+24 | | 7x-4x+3=x-6+9 | | 2x+3-1=2x-2-(-x) | | x^2-33x+540=0 | | 13=3r+5+r | | 6x+20=172-4y | | 8xy-5xy= | | 6x+8-2x=-7x-15+x | | 6x+3y-2z=7 | | 5=r+5-1 | | 7x-2=2+3 | | 3x^2-363= | | -2p+7=5-8p-3 | | 7-4[5-(6y-3)]= | | y=7(x+a) |